Effect of surface contamination on electron tunneling in the high bias range - Qin, Hailang (2013)
The effect of surface contamination on the electron tunneling in the high bias range is investigated from the perspective of ballistic electron emission microscopy (BEEM). A comparative BEEM study on the Au/SiO2/Si devices shows that there is a significant difference in the high bias range between the experiments performed with in situ and ex situ deposited Au. Detailed studies show that the difference arises from the contaminations during air exposure. These contaminations significantly accelerated the material transfer between the tip and the sample during tunneling and lead to the unreliability of BEEM studies in the high bias range on the ex situ prepared sample.